Análise exploratória de dados: uma abordagem com alunos do ensino médio - Vieira, Márcia (2008)
The object of the present paper is to study the interactions between the student and the environment of dynamic statistics, which, in this paper, will be the software Fathom, according to the approach of the Exploratory Data Analysis. We have discussed which concepts and procedures are necessary, aiming to the construction of critical analysis of a group of data, favored by the dynamism of the computational environment, which will be a tool to facilitate the mobilization of different types of registers of semiotic representations of this set. As theoretical reference, we have considered the levels proposed by Curcio (1989, 2001) to analyze the graphic comprehension mobilized by students in a situation of problem solving proposed in statistical context, and in the theory of Register of Semiotic Representation, by Duval (1994). We have tried, this way, to establish an understanding of this theory, largely used in researches in the Mathematics Education area relatively to geometric and algebraic concepts, this time to a representation of the statistics concept. We have especially tried to study the kinds of understanding of a picture, in this case, the kinds of understanding of statistical graphics or tables. In order to do so, we have elaborated a didactics sequence of activities developed with the use of the software, with bases on the Didactics Engineering (ARTIGUE, 1988). Before starting working with the activities of didactic sequence, we have realized a diagnostic test with the students, in which we were able to identify their main difficulties concerning statistical concepts. The development of the didactics sequence has shown that the interaction with the computerized environment and with the groups, in the articulations of different kinds of representation, have contributed to the comprehension of concepts as the arithmetic mean and median, and also with the analysis and interpretation of graphics of columns and dots (Dot-Plot). However, these variables are still insufficient to the comprehension of measures as quarts and the Box-Plot graphic